Interrogating race and racism - Agnew, Vijay, 1946- (Buffalo : University of Toronto Press, 2007)
Agnew delves into the public and private spheres of several distinct communities in order to expose the underlying inequalities within Canada's economic, social, legal, and political systems that frequently result in the denial of basic rights to migrant women.